Effectiveness of the Implementation of Additional Criminal Execution Replacement Money in Corruption Crimes - Achmad Surya; Firdaus Diezo (RESAM Jurnal Hukum, 2022)
In the process of recovering state financial losses, the Prosecutor's Office has an obligation to return state finances due to corruption. The purpose of this study is to examine the implementation of the additional criminal execution of substitute money and its obstacles by the Central Aceh District Attorney against corruption cases. This type of research is empirical normative research by analyzing primary data and secondary data. Data collection techniques used are direct interviews with informants and document studies. Furthermore, the collected data is processed by qualitative analysis. The execution of additional criminal compensation by the Central Aceh District Prosecutor's Office has been carried out well and effectively. Obstacles to the Central Aceh District Attorney's Office in carrying out additional criminal executions of replacement money, namely: First, the difficulty of tracing the assets of the suspect/defendant in an effort to recover state financial losses. Second, convicts of criminal acts of corruption prefer to undergo a subsidiary sentence of imprisonment/corporate law rather than paying replacement money.